Ethological notes: the interesting animal life - Arboccó de los Heros, Manuel (2015)
The behavior of animals has always captured the interest of man. One of the main causes of this is probably the adaptation that animals show, so often, in their acts; their similarities to us; or how they learn certain things. On the other hand, there has been an investigation to learn more about animals to also try to extrapolate part of the findings tohumans; and thus, to learn more about the Individual psychology and collective behavior. In this paper, we will single out anumber of peculiarities about animals, mention several characteristics of their behavior, point out the relationship between instinct, heritage and learning, and we will see if the findings have any relationship with human behavior.